2022
DOI: 10.1292/jvms.21-0539
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of seven nucleic acid amplification tests for detection of <i>Taylorella equigenitalis</i>

Abstract: Taylorella equigenitalis causes contagious equine metritis. Here we compared seven nucleic acid amplification tests for T. equigenitalis to select a rapid and reliable diagnostic method. The 95% detection limits of each assay varied greatly: real-time PCR had the lowest detection limit (0.77 fg/reaction); those of some of the conventional PCRs (cPCRs) were >100 fg/reaction. In experimentally infected samples, real-time PCR and semi-nested PCR showed the highest positive numbers (33 out of 42 samples), but two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Another group, Boyle et al [ 154 ], compared a previously reported Strangles LAMP assay [ 164 ] detecting the S. equi -specific gene, eqbE , to a real-time PCR assay that detects the seeI gene. However, this assay was not as analytically sensitive as the assay developed by Hobo et al [ 163 ], with a limit of detection of 1 CFU/mL.…”
Section: Loop-mediated Isothermal Amplification (Lamp) For Equine Bac...mentioning
confidence: 99%
“…Another group, Boyle et al [ 154 ], compared a previously reported Strangles LAMP assay [ 164 ] detecting the S. equi -specific gene, eqbE , to a real-time PCR assay that detects the seeI gene. However, this assay was not as analytically sensitive as the assay developed by Hobo et al [ 163 ], with a limit of detection of 1 CFU/mL.…”
Section: Loop-mediated Isothermal Amplification (Lamp) For Equine Bac...mentioning
confidence: 99%